Optimal design of low-voltage distribution networks for CO2 emission minimisation. Part II: Discrete optimisation of radial networks and comparison with alternative design strategies - Gan, Chin Kim (Institution of Engineering and Technology, 2011)
This study extends the model for optimal environmental design of distribution systems presented in Part I to network analyses. In particular, a specific algorithm is developed to apply the proposed circuit design for CO2 emission minimisation to radial networks, the great majority of low-voltage ones, taking into account the presence of only discrete capacities available for cable selection. The implementation of the network design algorithm is illustrated for a realistic large low-voltage urban network in a UK framework. The results found are compared to two benchmark networks designed according to a peak-based minimum investment strategy and an optimal economic strategy that minimises the network life-cycle cost. The specific emission reduction cost due to larger asset investment when applying an optimal environmental design strategy is then quantified with respect to the two alternative strategies. In addition, the results are checked against different discount rates that indicate the attitude of the network operator towards the cost of capital. The analyses illustrated provide clear-cut insights on the environmental and economic implications of adopting different design strategies (in particular, the optimal environmental one introduced here) and represent a key asset for network operators and policy makers in the path towards designing more sustainable energy systems.